Comparative analysis of learning curve in complex robot-assisted and laparoscopic liver resection. Issue 9 (September 2017) - Efanov, Mikhail; Alikhanov, Ruslan; Tsvirkun, Victor; Kazakov, Ivan; Melekhina, Olga; Kim, Pavel; Vankovich, Andrey; Grendal, Konstantin; Berelavichus, Stanislav; Khatkov, Igor
Abstract: Background: There is no comparative analysis of the learning curves for robot-assisted and laparoscopic liver resection. We aimed to compare learning curves in complex robotic and conventional laparoscopic liver resections with regards to estimation of the difficulty index score. Methods: The results of 131 consecutive liver resections were analyzed retrospectively (40 robot-assisted and 91 laparoscopic). The learning curve evaluation was based on calculation of procedures number before significant change of the difficulty index for minimally invasive liver resection or the rate of posterosuperior segments resection. Groups of early and late experience were compared in every type of approach (robot-assisted and laparoscopic). Results: Significant increase of difficulty index (from 5.0 [3.0–7.7] to 7.3 [4.3–10.2]) of robotic procedures required 16 procedures. It was necessary to perform 29 laparoscopic resections in order to significantly increase the rate of laparoscopic posterosuperior segments resection but without significant increase of difficulty index. The implementation of minimally invasive liver resection started with the robotic approach. Conclusion: The learning curve for robot-assisted liver resections is shorter in comparison with laparoscopic resections. The inclusion of robot-assisted resections in a minimally invasive liver surgery program may be useful to rapidly increase the complexity of laparoscopic liver resections.